STYLISTIC DEVICES IN BRITISH NEWSPAPER HEADLINES: A LINGUISTIC APPROACH (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the stylistic nature of British newspaper headlines through an analysis of rhetorical and linguistic techniques such as alliteration, metaphor, hyperbole, ellipsis, parallelism, irony, and antithesis. The study emphasizes how these devices serve both to attract reader attention and to compress information, creating impactful and memorable headlines. By evaluating selected examples from major British newspapers, this article reveals how stylistic choices in headlines influence public perception and enhance the communicative power of journalistic language.